PENERAPAN UI/UX PADA WEBSITE PENJUALAN ONLINE TOKO BANGUNAN ZULFAN REZQULLAH. - Djauhari, Teuku; Sany, Ezrifal; -, Sailani (LP2M Universitas Nurdin Hamzah, 2023)
Zulfan Rezqullah shop is a shop that sells various kinds of goods and building materials which was established in 2018, in the shop providing various kinds of equipment and building materials needed in the construction sector. Currently the Zulfan Rezqullah building shop still uses a manual system, starting from transactions, reports, entry and exit of goods and stock of goods is still manual and when serving some customers who buy goods in large quantities and with large nominalsthey still use notes, because the amount of data has accumulated and takes up a lot of space and uses paper making it difficult to find. Making an application at Zulfan Rezqullah's web-based building shop using system design and database design, User Experience User Interface design, using PhpMyAdmin and as a data storage medium, this system is made to be used by the admin. the researcher took the initiative to design a User Interface User Experience design for the sales application at the Zulfan Rezqullah building shop to make interactions between users and products easier, effective, and fun and also for users to access applications at the Zulfan Rezqullah building shop.